Transforming Migration Patterns through Digital Nomad Visa Policies in Strengthening the Digital Economy in the ASEAN Region - Hanafi, Muhammad Imran; Putri , Saskia Aulia; Cangara, Abdul Razaq; Asy'ari, Munjin Syafik (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2025)
Global dynamics show that human migration patterns continue to undergo transformation in line with technological developments. Whereas migration was previously explained through the traditional push and pull theory with a dominant pattern from the global north to the global south, new phenomena such as digital nomads have emerged as a form of change in the direction of migrant mobility. Digital nomads, who work remotely using digital technology, not only shape a new concept of migration, but also create added value for the digital economy of the destination country. To accommodate this phenomenon, a number of countries have begun to introduce digital nomad visa policies as a legal instrument that allows the digital nomad community to stay longer legally. Although the digital nomad visa policy has not yet become a joint ASEAN agenda, several countries in the Southeast Asian region have implemented this policy as part of their national interest strategy, such as Indonesia, Malaysia, and Thailand. This policy has the potential to support the growing trend of ASEAN competitiveness in the field of innovation. This article analyses the impact of policy implementation on the prospects for the digital economy in the Southeast Asian region. The results of the study show that the transformation of migration patterns through digital nomad visa policies has the potential to accelerate the flow of knowledge exchange and enhance the region's position in the global digital economy. However, its effectiveness is limited by the lack of harmonisation of regional regulatory frameworks and the readiness of digital infrastructure. Thus, this transformation of migration patterns not only changes the way individuals move and work, but also repositions the meaning of traditional migration, which plays a strategic role in the consolidation of the digital economy and ASEAN's regional competitiveness in the era of digital globalisation.